2001
DOI: 10.1046/j.1365-2265.2001.01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Marked improvement in cardiovascular function after successful transsphenoidal surgery in acromegalic patients

Abstract: We conclude that successful transsphenoidal surgery is able to induce a significant improvement in some cardiac parameters and a slight reduction in systolic blood pressure in acromegalic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
55
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 43 publications
7
55
0
6
Order By: Relevance
“…In fact, a significant decrease in SBP was observed by clinical measurement and confirmed by ABPM, extending our previous findings in a smaller series of cured patients (22,23), so that, according to current criteria (33), hypertension could be resolved in about 33% of patients defined as hypertensive by ABPM before surgery. In addition, in agreement with the findings of previous studies (14 -16), a blunted circadian BP rhythm was present in about 50% of the patients with active acromegaly, but was restored in 80% after surgery.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…In fact, a significant decrease in SBP was observed by clinical measurement and confirmed by ABPM, extending our previous findings in a smaller series of cured patients (22,23), so that, according to current criteria (33), hypertension could be resolved in about 33% of patients defined as hypertensive by ABPM before surgery. In addition, in agreement with the findings of previous studies (14 -16), a blunted circadian BP rhythm was present in about 50% of the patients with active acromegaly, but was restored in 80% after surgery.…”
Section: Discussionsupporting
confidence: 70%
“…In the present study, we first confirmed that successful TSS significantly improved cardiac abnormalities in patients with acromegaly (21-23), provided that strict criteria are retained to define surgical success (22,23). We decided to focus on LVM and diastolic function, because systolic function is normal at rest until a late stage of the disease (6) and ejection fraction was normal in all our study patients before surgery (data not shown).…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations